Deindustrialization: Why Would Anyone Consider It Is a Myth - Lošonc, Alpar; Ivanišević, Andrea (International Journal of Industrial Engineering and Management, 2014)
In this paper work we assemble the mosaic: we started with deindustrialization in the (negative) perspective of employment dynamics. We contextualized it here with indications of divergence between productivity and employment; it turned out that the productivity dynamics was not synchronized with the wage trends i.e. that the productivity is tied to significant asymmetry of distribution of productivity results. Deindustrialization occurs nowhere else but in this context; namely, in groups of different tendencies or, if we use our methodological projection, deindustrialization may be placed in the context of cumulative causal chains. Talking about deindustrialization without contextualizing shall not give us deeper explanations. Therefore, this is data that is worthy of full attention and do not allow us to get rid of the burden of speaking about deindustrialization too quickly. So, if we sum up everything said in this section, we may say and be able to see later as well, that there are certain differences, but globally speaking, there is no deindustrialization as a one-line process in terms of absolute drop in industrial employment. Article history: Received (17.11.2013); Revised (21.02.2014); Accepted (04.03.2014)